Self-medication Practice Among Undergraduate Medical Students in Nepalgunj Medical College, Chisapani - Singh, Ankita; Dhami, Dhabal Bahadur; Singh, Ritesh; Shah, Gaurav Jung (Journal of Nepalgunj Medical College, 2018)
Introduction: Self-medication forms an essential part of the self-care. Since medical students are being exposed to the knowledge of diseases and drugs, would assume a special significance to assess the self-medication practice among them.Methods: This was a cross-sectional study conducted from March to April 2018 in 200 preclinical medical students of Nepalgunj Medical College (NGMC), Chisapani. A structured questionnaire was used for data collection and the students who took self-medication within last two months were included.Result: Out of 200 students, 123 (61.5%) were found practicing self-medication. Majority of students (47.97%) were taking Non-steroidal Anti-inflammatory Drugs (NSAIDs) for fever (18.70%), headache (17.89%) and abdominal pain (13.01%). 21.14% of students were consuming paracetamol for these health ailments. 44.72% of students reported that they were practicing self-medication because of the mild nature of illness.Conclusion: Students are widely practicing self-medication, particularly NSAIDs group of drugs. In this situation, awareness about the pros and cons of self-medication should be must in the medical students.